The Impact of Government Policy on Curriculum Changes and Its Implications for the Quality of Islamic Religious Education in Elementary Schools - Syamsurizal, Oky; Helmiati, Helmiati; Hasyim, Hariza (Ar-Rosikhun: Jurnal Manajemen Pendidikan Islam, 2025)
Curriculum changes are part of the government's strategic policy to improve the quality of national education. This article aims to analyze government policies related to changes in the education curriculum over time until the birth of the Independent Curriculum, and examine its implications for improving the quality of Islamic Religious Education (PAI) learning in elementary schools. This study uses a qualitative approach with a library research method. Data were obtained from various written sources such as books, scientific journals, policy documents, and relevant laws and regulations, then analyzed using content analysis techniques. The results of the study indicate that curriculum changes in Indonesia, starting from the 1994 Curriculum, the 2004 KBK, the 2006 KTSP, the 2013 Curriculum, and the Independent Curriculum, reflect the government's ongoing efforts to adapt education to current developments and student needs. The implementation of the Independent Curriculum has positive implications for Islamic Religious Education (PAI) learning in elementary schools, especially in encouraging more flexible, contextual, and student-centered learning. This curriculum opens up space for Islamic Religious Education (PAI) teachers to innovate through project-based learning and authentic assessment, thus enhancing not only knowledge but also students' religious attitudes and noble morals. Therefore, the Independent Curriculum has the potential to holistically improve the quality of Islamic Religious Education (PAI) learning if supported by teacher and school readiness